2001
DOI: 10.1016/s0079-6107(01)00014-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the radical enzyme ribonucleotide reductase

Abstract: Ribonucleotide reductases (RNRs) catalyze all new production in nature of deoxyribonucleotides for DNA synthesis by reducing the corresponding ribonucleotides. The reaction involves the action of a radical that is produced differently for different classes of the enzyme. Class I enzymes, which are present in eukaryotes and microorganisms, use an iron center to produce a stable tyrosyl radical that is stored in one of the subunits of the enzyme. The other classes are only present in microorganisms. Class II enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
360
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 299 publications
(366 citation statements)
references
References 215 publications
4
360
0
Order By: Relevance
“…Their cofactors contain a tyrosyl radical and a diferric iron center, which generate a thiyl radical C439 in the R1 subunit. 1,[10][11][12] The prototype of Class II RNRs was isolated from Lactobacillus leichmannii.…”
Section: Ribonucleotide Reductases: Function and Structurementioning
confidence: 99%
See 4 more Smart Citations
“…Their cofactors contain a tyrosyl radical and a diferric iron center, which generate a thiyl radical C439 in the R1 subunit. 1,[10][11][12] The prototype of Class II RNRs was isolated from Lactobacillus leichmannii.…”
Section: Ribonucleotide Reductases: Function and Structurementioning
confidence: 99%
“…Adenosylcobalamin (AdoCbl), or coenzyme B 12 , acts as a cofactor for this monomeric enzyme. It has been suggested that AdoCbl abstracts the hydrogen atom from the cysteine residue (cys408) in the R1 subunit to form a thiyl radical, generating cob(II)alamin and, supposedly, an 5'-deoxyadenosyl radical.…”
Section: Ribonucleotide Reductases: Function and Structurementioning
confidence: 99%
See 3 more Smart Citations